2006
DOI: 10.1002/bdra.20283
|View full text |Cite
|
Sign up to set email alerts
|

Chick embryos exposed to trichloroethylene in an ex ovo culture model show selective defects in early endocardial cushion tissue formation

Abstract: The regional selectivity of these effects in the chick heart suggests a critical window of susceptibility to TCE in the epithelial-mesenchymal transformation of atrioventricular canal endocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
3
17
1
Order By: Relevance
“…Additionally, the time-course experiments confirmed the results obtained with the 10 ppb TCE exposure (24 h) and indicated that exposure to low concentrations of TCE exerts a long-lasting effect (at least 72 h) on expression levels of the tested genes. Overall, our results are in agreement with data recently published by Drake et al [8,42] and Mishima et al [9] reporting that the effects of TCE on chick cardiac development were dose-and stage-specific. Importantly, our observed alterations in gene expression level between 1 and 10 ppb TCE are consistent with Drake's reported effects on valvuloseptal hypercellularity and reduced hemodynamics in chick embryos exposed to 8 ppb TCE.…”
Section: Real-time Pcr Analysissupporting
confidence: 96%
See 1 more Smart Citation
“…Additionally, the time-course experiments confirmed the results obtained with the 10 ppb TCE exposure (24 h) and indicated that exposure to low concentrations of TCE exerts a long-lasting effect (at least 72 h) on expression levels of the tested genes. Overall, our results are in agreement with data recently published by Drake et al [8,42] and Mishima et al [9] reporting that the effects of TCE on chick cardiac development were dose-and stage-specific. Importantly, our observed alterations in gene expression level between 1 and 10 ppb TCE are consistent with Drake's reported effects on valvuloseptal hypercellularity and reduced hemodynamics in chick embryos exposed to 8 ppb TCE.…”
Section: Real-time Pcr Analysissupporting
confidence: 96%
“…Recently, the National Academy of Sciences issued a report [7] suggesting TCE exerts negative effects on cardiac development, particularly in avian models. In addition, two groups provided independent observations indicating that TCE specifically alters endocardial cushion formation in chick embryos [8,9]. These results are in line with previous data obtained from Boyer et al [10], suggesting that TCE disrupts the endothelial mesenchymal transition (EMT), a process involved in formation of the endocardial cushion in chick embryos.…”
Section: Introductionsupporting
confidence: 91%
“…CYP2E1 was implicated as the major TCE metabolizing CYP in both human liver microsomes and the murine model systems, while CYP2E1 is present in low levels in human fetal liver and brain (Brzezinski et al, 1999; Carpenter et al, 1996). We, and others, found that TCE affects cardiovascular development prior to both liver and brain development (Drake et al, 2006b; Makwana et al, 2010; Mishima et al, 2006). If metabolic activation of TCE is relevant to teratogenesis, then the existence and localization of cytochrome P450 enzymes in the early embryo is important to examine.…”
Section: Introductionmentioning
confidence: 68%
“…More recently several groups have reported on possible mechanisms by which TCE may affect heart development. In the chick model, Boyer et al (2000) demonstrated that exposure to 200ppb TCE reduced by 50% EMT of valve progenitors in a collagen gel assay, while lower doses of TCE in ovo enhanced valvuloseptal hypercellularity, endocardial cell proliferation and altered hemodynamic in the embryonic heart (Drake et al, 2006a; Drake et al, 2006b; Mishima et al, 2006). Others found that TCE exposure altered expression of the endothelial nitric oxide synthase and disrupted VEGF-stimulated endothelial proliferation in myocytes, suggesting a possible mechanism for TCE-mediated heart malformations (Ou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%